Four-jointed is required for intermediate growth in the proximal-distal axis in Drosophila. - Villano, J.L.; Katz, F.N. (Development, 1995)
Genes capable of translating positional information into regulated growth lie at the heart of morphogenesis, yet few genes with this function have been identified. Mutants in the Drosophila four-jointed (fj) gene show reduced growth and altered differentiation only within restricted sectors of the proximal-distal (PD) axis in the leg and wing, thus fj is a candidate for a gene with this coordination function. Consistent with a position-sensitive role, we show that fj is expressed in a regional pattern in the developing leg, wing, eye and optic lobe. The fj gene encodes a novel type II membrane glycoprotein. When the cDNA is translated in an in vitro translation system in the presence of exogenous microsomal membranes, the intralumenal portion of some of the molecules is cleaved, yielding a secreted C-terminal fragment. We propose that fj encodes a secreted signal that functions as a positive regulator of regional growth and differentiation along the PD axis of the imaginal discs.